Risk-Based Disaster Financing Governance: Assessing the Effectiveness of On-Call Funds, Village Funds, and Regional Budgets for Disaster Risk Reduction - Mujahidin; Lalu Ahmad Murdhani (International Journal of Scientific Research, 2026)
This study examines risk-based disaster financing governance by analyzing the effectiveness of on-call funds, village funds, and regional budgets in disaster risk reduction. The study is based on the argument that disaster financing should not be understood only as an emergency response mechanism, but also as a preventive governance instrument for reducing vulnerability, strengthening preparedness, and improving regional resilience. Using a qualitative case study approach, this research analyzes how disaster financing instruments are planned, allocated, coordinated, implemented, and evaluated at the local government level. Data were collected through in-depth interviews, field observations, and document analysis involving local disaster management agencies, regional planning agencies, financial management agencies, village governments, sectoral offices, disaster volunteers, and community representatives in disaster-prone areas. The findings show that on-call funds are effective in supporting rapid emergency response, but their contribution to long-term risk reduction remains limited when not supported by preventive financing. Village funds have significant potential for community-based mitigation and preparedness, yet their effectiveness depends on risk-informed village planning and technical capacity. Regional budgets can finance broader cross-sectoral risk reduction, but their implementation is often fragmented across institutions. This study proposes a risk-based disaster financing governance framework that connects risk assessment, fiscal planning, budget allocation, implementation, monitoring, and outcome-based accountability. The novelty of this study lies in shifting disaster financing analysis from reactive emergency expenditure toward preventive investment for disaster risk reduction and regional resilience.